Raw and analysed data for four ammonia removal technologies treating THP/AD dewatering liquors - Ochs, Pascal; Soares, Ana; Stephenson, Tom; Martin, Benjamin D.; Germain, Eve; van Loosdrecht, Mark C. M. (Cranfield University, 2020)
The data set contains influent, effluent and performance data for the paper "Ammonia removal from thermal hydrolysis dewatering liquors via three different deammonification technologies". The data is stored in an excel spreadsheet including raw data, cleaned up data and details to analysis.
Keywords: deammonification'; 'thermal hydrolysis process'; 'THP/AD'; 'sequencing batch reactor'; 'moving bed biofilm reactor'; 'suspended sludge'; 'granular sludge'; 'Wastewater Treatment Processes'